Production process of packaging-grade expandable polystyrene particles
By adopting the packaging-grade radiant polystyrene granules process in the production of polystyrene packaging materials, the uniform dispersion of emulsifiers and dispersants and the impact resistance of high-impact polystyrene, combined with the foaming effect of pentane, It solves the problem of high styrene residual monomer and pentane content in traditional materials, and achieves efficient and environmentally friendly production and product performance improvement.
Patent Information
- Application Number
- CN202411379541.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The high content of low volatile organics such as styrene residue monomer and pentane in traditional polystyrene packaging materials, resulting in environmental pollution and low production efficiency.
Using a production process of packaging grade radiable polystyrene particles, by mixing pure water, emulsifier and dispersant, styrene monomer and high impact polystyrene, control the temperature and reaction conditions, and add pentane as The foaming agent, using antistatic agents and external lubricants, ensures the uniform dispersion of styrene monomers and the stability of polymerization reaction, and reduces the residual monomers and the content of low volatile components.
Improve the mechanical strength and foaming ratio of the emitable polystyrene, reduce the content of styrene residual monomer and pentane, realize an environmentally friendly and efficient production process, meet the requirements of Reach and ROHS certification, and improve the quality of the product and Productivity.
Smart Images

Figure BDA0005069556740000091 
Figure BDA0005069556740000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and more specifically, to a production process of packaging-grade expandable polystyrene particles. Background Art
[0002] Expandable Polystyrene (EPS) is made of pure water, styrene, benzoyl peroxide, tert-butyl percarbonate, pentane and structural regulators, and is made through stirring, heating, suspension polymerization, washing, screening and other steps. Expandable polystyrene beads containing a foaming agent can be made into foamed plastic products through pre-foaming, aging and foam molding. Foamed polystyrene foam products are currently very valuable insulation, heat insulation, thermal insulation and packaging cushioning materials. Polystyrene foam has low water absorption, heat insulation, excellent dielectric properties and high mechanical strength, and is widely used in construction, packaging, model making and other fields.
[0003] Traditional polystyrene packaging materials are lightweight, have excellent cushioning properties and good thermal insulation properties, but have the disadvantages of high residual styrene content and high content of low-volatile organic compounds such as pentane. Summary of the invention
[0004] In order to improve the problems of high residual styrene and high content of low-volatile organic compounds such as pentane, the present application provides a production process for packaging-grade expandable polystyrene particles.
[0005] In a first aspect, the present application provides a production process for packaging-grade expandable polystyrene particles, which adopts the following technical solution: A production process for packaging-grade expandable polystyrene particles comprises the following steps: (1) Pure water, emulsifier and dispersant are mixed evenly, pH is controlled at 7-9, styrene monomer is added, and then nucleating agent, initiator and high impact polystyrene are added, steam heating is started, and the temperature rise rate is controlled at 0.5-0.6°C / min. The entire steam heating time is 1.5-2h. When the temperature reaches 84-85°C, the steam is stopped. When the temperature reaches 87-89°C, circulating cooling water is passed to maintain the temperature at 90±0.5°C; (2) performing a low-temperature granulation reaction. After the low-temperature granulation is completed, pentane is added to perform a high-temperature reaction. The temperature is raised to 120.5-122.5°C at a rate of 0.5-0.6°C / min, and the reaction time is 2.5-4h. The temperature is lowered to below 53°C, and the calcium is neutralized with hydrochloric acid for washing. The washing pH is controlled to be 4.0-6.0. The product is separated and dried, sprayed with an antistatic agent, dried twice, sieved, and an external lubricant is added.
[0006] By adopting the above technical solution, the emulsifier can improve the surface properties of the styrene monomer, stabilize the dispersion system, ensure the uniform dispersion of the styrene monomer in the water phase, prevent the formation of aggregates, and thus obtain particles with uniform particle size; and the emulsifier helps the uniform distribution of the foaming agent inside the particles, ensuring the controllability of the foaming process and the improvement of the foaming ratio. The dispersant further ensures the uniform dispersion of the styrene monomer in the water phase, prevents the formation of aggregates, and thus obtains particles with uniform particle size, which helps the stable dispersion of the styrene monomer in the water phase, provides a stable environment for the polymerization reaction, and promotes the polymerization reaction.
[0007] High-impact polystyrene has good impact resistance and toughness. Adding high-impact polystyrene can improve the mechanical strength of expandable polystyrene and increase the durability of expandable polystyrene. The addition of high-impact polystyrene can also improve the processing performance of expandable polystyrene, making it more stable during the foaming process, helping to control the density and uniformity of the foam and enhance the comprehensive performance of expandable polystyrene. Nucleating agents can promote the crystallization process of polystyrene, help to form smaller and more uniform grains, increase the crystallization rate and transparency, thereby improving the physical properties of the material such as hardness and rigidity, and help to enhance the mechanical properties of polystyrene such as tensile strength and impact resistance. Initiators can provide free radicals or ions to initiate the polymerization reaction of styrene monomers, form polystyrene polymer chains, control the rate of polymerization, improve the efficiency of polymerization, reduce unreacted monomer residues, and increase the yield of polymers.
[0008] Pentane is used as a foaming agent. When the polystyrene beads expand under heating conditions, pentane vaporizes due to heat, generates pressure, causes the beads to expand and form a cellular structure, and gives the expandable polystyrene material the characteristics of light weight, heat insulation and sound insulation. Antistatic agents can increase the conductivity of the surface of expanded polystyrene, so that static charges can be dissipated faster, thereby reducing static electricity accumulation. External lubricants can reduce the viscosity of polystyrene melts, improve its fluidity during processing, and make the material flow more easily in the mold, thereby improving production efficiency, reducing friction between the polymer and processing equipment, reducing wear, and extending the service life of the equipment. The expandable polystyrene particles obtained by the above-mentioned preparation process have a high foaming ratio, are environmentally friendly, have a simple molding process, low styrene residual monomers, and low content of low-volatile organic matter such as pentane. The continuous process ensures product quality stability and consistency and improves production efficiency.
[0009] Optionally, the following raw materials are included, calculated by weight: 104-106 parts of pure water, 0.002-0.003 parts of emulsifier, 0.1-0.2 parts of dispersant, 100-102 parts of styrene monomer, 0.28-0.36 parts of initiator, and 0.5-1 parts of high impact polystyrene.
[0010] By adopting the above technical scheme, the amount of each raw material is further limited, so that the prepared expandable polystyrene particles have high mechanical properties such as tensile strength and impact resistance. The various components cooperate with each other and work together. The nucleating agent can promote the crystallization process of polystyrene and increase the crystallization rate. The dispersant can stabilize the dispersion system and ensure the uniform dispersion of styrene monomer in the aqueous phase. The emulsifier helps to stably disperse the styrene monomer in the aqueous phase and provide a stable environment for the polymerization reaction. The expandable polystyrene particles prepared by the combination of the various components have a high foaming ratio, low styrene residual monomer, and low content of low-volatile organic matter such as pentane, thereby improving the production efficiency of the expandable polystyrene particles.
[0011] Optionally, the emulsifier is one or more of gelatin, cellulose, and polyvinyl alcohol; the external lubricant is one or more of mono- and di-glycerides, triolein, zinc stearate, and low-density polyethylene wax.
[0012] By adopting the above technical solution, gelatin can be adsorbed on the surface of styrene monomer droplets to form a protective film, which prevents the monomer droplets from aggregating and merging in the water phase, and makes the styrene monomer dispersed evenly in the water phase, thereby stabilizing the emulsion system. Cellulose can also be adsorbed on the surface of styrene monomer droplets to form a protective film, which prevents the monomer droplets from aggregating and merging in the water phase, and makes the styrene monomer dispersed more evenly in the water phase, thereby improving the polymerization efficiency and improving the thermal stability and mechanical properties of the polymer. Polyvinyl alcohol acts as an emulsifier and stabilizer to form a gel system with a higher viscosity. During the emulsion polymerization process, a more stable emulsion system can be formed. They form a composite protective layer on the surface of the monomer droplets, which effectively prevents the monomer droplets from aggregating and merging in the water phase, thereby improving the stability of the emulsion.
[0013] The external lubricant forms a lubricating layer on the surface of expandable polystyrene particles, improving the fluidity of the particles, preventing adhesion between particles, making them easier to flow during processing such as extrusion and injection molding, reducing the friction of particles during processing, thereby improving processing speed and product quality.
[0014] Optionally, the nucleating agent is 0.1-0.2 parts of polyethylene wax, 0.06-0.1 parts of phosphate, and 0.01-0.02 parts of potassium salt.
[0015] By adopting the above technical scheme, the dosage of polyethylene wax, potassium salt and phosphate is further limited. The crystalline structure of polyethylene wax can promote the formation of bubble nuclei during the polymerization process of expandable polystyrene beads. When the expandable polystyrene beads expand during heating, the polyethylene wax helps to form a more uniform and stable pore structure, thereby improving the foaming quality of the expandable polystyrene material. In addition, polyethylene wax can also improve the fluidity of expandable polystyrene beads, which helps to improve production efficiency and product quality.
[0016] During the polymerization process of expandable polystyrene beads, phosphates can promote the formation of pores, make the pores more uniform, and help control the size and distribution of the pores, thereby affecting the density, strength and thermal insulation properties of the expandable polystyrene material. In addition, phosphates play a role in the flame retardant properties of expandable polystyrene, improving the safety of the material.
[0017] Potassium salts promote and control the formation of polymer crystals. As heterogeneous nucleating agents, they provide heterogeneous nucleation sites for crystallization, accelerate the crystallization process of polymers, and shorten the crystallization time. The mixed use of polyethylene wax, potassium salts, and phosphates plays a synergistic role in the production process of expandable polystyrene, and jointly improves the foaming performance and physical properties of expandable polystyrene materials. Potassium salts, as heterogeneous nucleating agents, can provide heterogeneous nucleation sites for crystallization and accelerate the crystallization process of polymers. The addition of polyethylene wax and phosphates can further promote crystallization, shorten the crystallization time, and increase the degree of crystallinity by affecting the crystallization kinetics, while improving the density, strength, and thermal insulation properties of expandable polystyrene materials, as well as enhancing their flame retardant safety.
[0018] Optionally, the initiator is one or more of benzoyl peroxide, tert-butyl percarbonate, and tert-butyl perbenzoate.
[0019] By adopting the above technical solution, the initiator decomposes under thermal conditions to produce free radicals, which can initiate the polymerization reaction of styrene monomers to form polystyrene chains. The decomposition of the initiator also produces gases, such as carbon dioxide, which form tiny bubbles in the polymer, causing the polystyrene particles to expand and form a lightweight foaming material.
[0020] Optionally, the dispersant is tricalcium phosphate or hydroxyapatite.
[0021] By adopting the above technical solution, the dispersant reduces the surface tension between the expandable polystyrene particles, prevents the particles from agglomerating during processing, and ensures that the particles are evenly dispersed in the molten state, thereby improving the processing performance of the material and the quality of the final product; it can also improve the fluidity of the expandable polystyrene melt, making it easier to flow and fill the mold during processing, thereby improving production efficiency, while reducing shear stress during processing and reducing energy consumption.
[0022] Optionally, in step (2), 6-10 parts of modified glass fiber are also added, and the pretreatment method of the modified glass fiber comprises the following steps: dispersing the glass fiber in a citric acid solution, soaking for 1-2 hours, washing with water, and then dispersing it in deionized water, adding modified silica, stirring evenly, filtering, and then spraying a chitosan aqueous solution, and drying to obtain the modified glass fiber.
[0023] By adopting the above technical solution, citric acid corrodes the surface of the glass fiber, removes impurities and organic matter on the surface of the glass fiber, increases the specific surface area of the glass fiber, makes the glass fiber uneven, and helps the subsequent reaction of the glass fiber with other components.
[0024] Modified silica has a high specific surface area, high porosity and good chemical stability. It can be loaded on the surface and voids of glass fibers to increase the strength of glass fibers. It is subsequently applied to expandable polystyrene to improve the compressive and tensile strengths of expandable polystyrene, making it less likely to deform or be damaged when subjected to external forces.
[0025] Chitosan has a certain viscosity. Spraying chitosan aqueous solution makes the modified silica and glass fiber more bonded, so that the modified silica is stably loaded on the surface of the glass fiber, which increases the stability of the performance of the glass fiber. It is subsequently applied to expandable polystyrene to improve the corresponding properties of expandable polystyrene.
[0026] Optionally, the mass ratio of the glass fiber, modified silica and chitosan aqueous solution is 1 g: 0.5-0.8 g: 0.03-0.06 mL.
[0027] By adopting the above technical scheme, the mass ratio of glass fiber, modified silica and chitosan aqueous solution is further limited within a certain range, thereby improving the mechanical strength and mechanical properties of the glass fiber. The modified silica is loaded on the surface and gaps of the glass fiber to improve the strength of the glass fiber. Chitosan makes the modified silica and glass fiber more bonded, and subsequently improves the mechanical properties of expandable polystyrene, which is conducive to the application of expandable polystyrene.
[0028] Optionally, the method for preparing the chitosan aqueous solution comprises the following steps: dispersing chitosan in an acetic acid solution, adding sodium alginate, and stirring uniformly to obtain the chitosan aqueous solution.
[0029] By adopting the above technical scheme, chitosan is dispersed in acetic acid solution to form a uniform solution, and sodium alginate is added. Sodium alginate has good film-forming and gel-forming abilities. It is mixed and cross-linked with chitosan to improve the viscosity of chitosan and form a gel-like structure, thereby increasing the viscosity of the system, which is subsequently helpful to improve the adhesion between glass fiber and modified silica. Moreover, the mixture of sodium alginate and chitosan further improves the mechanical strength and toughness of chitosan, making it less likely to break or deform when subjected to external force, thereby improving the corresponding properties of the modified glass fiber, which is subsequently applied to expandable polystyrene to improve the corresponding properties.
[0030] Preferably, the preparation method of the modified silica comprises the following steps: dispersing silica in a silane coupling agent solution, stirring at a temperature of 70-75° C. for 1-2 hours, then adding graphene and calcium stearate, stirring evenly, and drying to obtain modified silica.
[0031] By adopting the above technical scheme, the silane coupling agent improves the surface properties of silica, improves the dispersibility of silica in the organic matrix, prevents agglomeration, and makes silica easier to cooperate with other components. Graphene can be loaded on the surface of silica, which increases the tensile strength and impact strength of silica. Calcium stearate is used as a surfactant to further improve the dispersibility of silica and graphene, so that graphene is more evenly distributed on the surface of silica, thereby improving the performance stability of the modified silica, which will subsequently help to improve the mechanical properties and stability of glass fiber.
[0032] Preferably, the mass ratio of white carbon black, graphene and calcium stearate is 1g:25-30mg:0.1-0.3g.
[0033] By adopting the above technical scheme, the mass ratio of silica, graphene and calcium stearate is further limited within a certain range, the tensile strength, modulus and toughness of silica are improved, graphene can be loaded on the surface of silica, the tensile strength and impact strength of silica are increased, calcium stearate makes silica and graphene dispersed evenly, so that graphene is more evenly distributed on the surface of silica, and the combination of silica, graphene and calcium stearate improves the mechanical properties of silica, and subsequently improves the corresponding properties of glass fiber.
[0034] In summary, this application has the following beneficial effects: 1. In this application, a one-step process is adopted, and the monomer styrene, water system (emulsifier, dispersant), and oil system (initiator) are intermittently produced by suspension polymerization. With the help of mechanical stirring force, the monomer is dispersed in water in the form of droplets to carry out suspension polymerization reaction. The reacted materials are washed, centrifugally dried, sieved, coated, weighed, packaged, and inspected before being stored in a finished product warehouse.
[0035] 2. In this application, the low components in the finished product are collected and incinerated through the micro-negative pressure system produced, and non-benzene ring high-temperature initiators are used to avoid the decomposition residue of the initiator. Environmentally friendly auxiliary materials are used (dispersants and calcium carbonate are both certified by Europe) to meet the requirements of Reach and ROHS certification and reduce the impact on the environment.
[0036] 3. This application eliminates the use of plasticizers such as toluene / xylene and phthalates, effectively solving the problem of plasticizer residues. The nucleating agent is improved, the traditional sulfur-containing nucleating agent is eliminated, and odorless phosphate is used as the nucleating agent. The emulsifier uses one or more of gelatin, polyvinyl alcohol, and cellulose, avoiding the high difficulty of wastewater treatment with sodium benzenesulfonate emulsifiers. DETAILED DESCRIPTION
[0037] Preparation example of modified glass fiber Preparation Example 1-1 The pretreatment method of modified glass fiber comprises the following steps: dispersing 1.2 kg of glass fiber in 2 L of 20% by mass citric acid solution, soaking for 2 hours, washing with water, and then dispersing in 1.8 L of deionized water, adding modified white carbon black, stirring evenly, filtering, and then spraying a chitosan aqueous solution, and drying to obtain modified glass fiber.
[0038] The mass ratio of glass fiber, modified silica and chitosan aqueous solution is 1g:0.5g:0.06mL.
[0039] The preparation method of chitosan aqueous solution comprises the following steps: dispersing 1 kg chitosan in 1.3 L acetic acid solution with a mass fraction of 26%, adding 0.3 kg sodium alginate, stirring evenly, and obtaining chitosan aqueous solution.
[0040] The preparation method of modified white carbon black comprises the following steps: dispersing 1.1 kg white carbon black in 1.5 L of 0.2% by mass silane coupling agent KH570 solution, stirring at a temperature of 75° C. for 2 hours, then adding graphene and calcium stearate, stirring evenly, and drying to obtain modified white carbon black.
[0041] The mass ratio of white carbon black, graphene and calcium stearate is 1g:25mg:0.1g.
[0042] Preparation Example 1-2 The difference from Preparation Example 1-1 is that no modified silica is added.
[0043] Preparation Example 1-3 The difference from Preparation Example 1-1 is that the chitosan aqueous solution is not sprayed.
[0044] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, modified silica and chitosan aqueous solution is 1 g:0.8 g:0.03 mL.
[0045] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of glass fiber, modified silica and chitosan aqueous solution is 1 g:0.1 g:0.12 mL.
[0046] Preparation Example 1-6 The difference from Preparation Example 1-1 is that sodium alginate is not added in the preparation method of the chitosan aqueous solution.
[0047] Preparation Example 1-7 The difference from Preparation Example 1-1 is that graphene is not added in the preparation method of modified silica.
[0048] Preparation Example 1-8 The difference from Preparation Example 1-1 is that calcium stearate is not added in the preparation method of modified silica.
[0049] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of white carbon black, graphene and calcium stearate is 1g:30mg:0.3g.
[0050] Preparation Example 1-10 The difference from Preparation Example 1-1 is that the mass ratio of white carbon black, graphene and calcium stearate is 1g:20mg:0.6g. Example
[0051] Example 1 A production process for packaging-grade expandable polystyrene particles comprises the following steps: (1) Pure water, emulsifier and dispersant were mixed evenly, pH was controlled at 9, styrene monomer was added, and then nucleating agent, initiator and high impact polystyrene were added, steam heating was started, and the temperature rise rate was controlled at 0.5°C / min. The whole steam heating time was 1.5h. When the temperature reached 84°C, the steam was stopped. When the temperature reached 87°C, circulating cooling water (circulating water temperature was controlled at 30°C) was passed to maintain the temperature at 90.5°C; (2) Perform low-temperature granulation reaction. After the low-temperature granulation is completed, 4 kg of pentane is added to perform high-temperature reaction. The temperature is raised to 120.5 ° C. at a rate of 0.5 ° C. / min. The reaction time is 2.5 h. The temperature is lowered to 50 ° C. The calcium is neutralized with hydrochloric acid and washed. The washing pH is controlled to 4.0. Separate and dry, spray with an antistatic agent, dry twice, sieve, and add an external lubricant to obtain.
[0052] Calculated by weight, the following raw materials are included: 104kg pure water, 0.002kg emulsifier, 0.1kg dispersant, 100kg styrene monomer, 0.02kg antistatic agent, 0.25kg external lubricant, and 0.5kg high-impact polystyrene. The high-impact polystyrene comes from Zhejiang Yisu New Material Technology Co., Ltd.
[0053] The dispersant is tricalcium phosphate; the emulsifier is gelatin, the external lubricant is zinc stearate; and the antistatic agent is ethylene dioctadecyl quaternary ammonium salt.
[0054] The nucleating agent is 0.2 kg of polyethylene wax, 0.1 kg of phosphate, and 0.02 kg of potassium salt. The phosphate is sodium dihydrogen phosphate, and the potassium salt is potassium sulfate.
[0055] The initiator is benzoyl peroxide.
[0056] Example 2 A production process for packaging-grade expandable polystyrene particles comprises the following steps: (1) Pure water, emulsifier and dispersant were mixed evenly, pH was controlled to 7, styrene monomer was added, and then nucleating agent and initiator were added, steam heating was started, and the temperature rise rate was controlled to be 0.6°C / min. The whole steam heating time was 2h. When the temperature reached 85°C, the steam was stopped. When the temperature reached 89°C, circulating cooling water (circulating water temperature was controlled at 30°C) was passed to maintain the temperature at 89.5°C; (2) Perform low-temperature granulation reaction. After the low-temperature granulation is completed, 5 kg of pentane is added to perform high-temperature reaction. The temperature is raised to 122.5 ° C at a rate of 0.6 ° C / min. The reaction time is 4 hours. The temperature is lowered to 50 ° C. The calcium is neutralized with hydrochloric acid and washed. The washing pH is controlled to 6.0. Separate and dry, spray with an antistatic agent, dry twice, sieve, and add an external lubricant to obtain.
[0057] Calculated by weight, the following raw materials are included: 106 kg pure water, 0.003 kg emulsifier, 0.2 kg dispersant, 102 kg styrene monomer, 0.03 kg antistatic agent, 0.3 kg external lubricant, and 1 kg high impact polystyrene.
[0058] The nucleating agent is 0.1 kg polyethylene wax, 0.06 kg phosphate, and 0.01 kg potassium salt.
[0059] Example 3 A production process for packaging-grade expandable polystyrene particles, which differs from Example 1 in that modified glass fiber is added in step (2), and the modified glass fiber adopts the preparation example 1-1.
[0060] Example 4 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Example 1-2.
[0061] Example 5 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-3.
[0062] Example 6 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-4.
[0063] Example 7 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-5.
[0064] Example 8 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-6.
[0065] Example 9 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-7.
[0066] Example 10 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-8.
[0067] Embodiment 11 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-9.
[0068] Example 12 A production process for packaging-grade expandable polystyrene particles, which differs from Example 3 in that the modified glass fiber adopts Preparation Examples 1-10.
[0069] Embodiment 13 A production process for packaging-grade expandable polystyrene particles, which differs from Example 1 in that polyethylene wax is not added.
[0070] Embodiment 14 A production process for packaging-grade expandable polystyrene particles, which differs from Example 1 in that sodium dihydrogen phosphate is not added.
[0071] Embodiment 15 A production process for packaging-grade expandable polystyrene particles, which differs from Example 1 in that potassium sulfate is not added.
[0072] Comparative Example Comparative Example 1 Example 1 in patent CN 117487236A is used as comparative example 1 of the present application.
[0073] Performance testing The expandable polystyrene particles prepared in Examples 1-15 and Comparative Example 1 were subjected to performance tests.
[0074] 1. Determination of residual styrene: The content of residual monomers in polystyrene was determined by gas chromatography. The test instrument used was a GC-8900 gas chromatograph equipped with an HP19395A headspace sampler and propylene oxide as the solvent. The test conditions were: the detector temperature was 180°C, the thermal equilibrium time was 50 min, the headspace heating temperature was 120°C, and 1,2,4-trimethylbenzene was used as the internal standard with a purity of not less than 99%.
[0075] 2. The thermal conductivity shall be determined in accordance with GB / T 10801-2006 "Determination of thermal conductivity and thermal resistance of extruded polystyrene foam plastics", the flexural strength shall be determined in accordance with GB / T 8812-2007, the compressive strength shall be determined in accordance with GB / T 8813-2020 "Determination of compression properties of rigid foam plastics", and the tensile strength at break shall be determined in accordance with ASTM-D3575.
[0076] Table 1 Test data of embodiments and comparative examples Combining the examples and the data in Table 1, it can be seen that the production process of the packaging-grade expandable polystyrene particles prepared in Examples 1-2 has less residual monomers, better mechanical properties and thermal insulation. Among them, the residual monomer of Example 1 is 0.04%, the thermal conductivity is 0.037W / m﹒k, the bending strength is 545KPa, the compressive strength is 115KPa, and the tensile strength at break is 507KPa, indicating that the preparation process of the present application reduces the residual rate of styrene, and the prepared expandable polystyrene particles have better mechanical properties. Various components cooperate with each other to jointly improve the mechanical strength and chemical stability of expandable polystyrene.
[0077] Comparative Example 1 is Example 1 in patent CN 117487236A. As can be seen from Table 1, the residual monomer of Example 1 is 0.05%, the flexural strength is 520 KPa, and the tensile strength at break is 510 KPa, indicating that the expandable polystyrene particles prepared by the preparation process of the present application have a lower styrene residual rate, and the prepared expandable polystyrene particles have good mechanical properties, thereby expanding the application of expandable polystyrene particles.
[0078] In Example 3, Example 6, and Example 11, the preparation process of expandable polystyrene particles further includes adding modified glass fiber in step (1). As can be seen from Table 1, the residual monomer of Example 3 is 0.05%, the thermal conductivity is 0.031 W / m﹒ k, the flexural strength is 568 KPa, the compressive strength is 137 KPa, and the tensile strength at break is 530 KPa, indicating that the modified glass fiber has high strength and is subsequently applied to expandable polystyrene to improve the compressive strength and tensile strength of expandable polystyrene, so that it is not easily deformed or damaged when subjected to external force.
[0079] In the pretreatment method of the modified glass fiber in Example 4, no modified silica is added. In the pretreatment method of the modified glass fiber in Example 5, no chitosan aqueous solution is added. As can be seen from Table 1, compared with Example 3, the residual monomer and thermal conductivity do not change much, but the numerical changes in flexural strength, compressive strength and tensile strength at break are significantly reduced, indicating that the modified silica has a high specific surface area, high porosity and good chemical stability, can be loaded on the surface and voids of the glass fiber, and improve the strength of the glass fiber. Spraying the chitosan aqueous solution makes the modified silica and the glass fiber more bonded, so that the modified silica is stably loaded on the surface of the glass fiber, which increases the stability of the performance of the glass fiber, and is subsequently applied to expandable polystyrene to improve the corresponding properties of expandable polystyrene.
[0080] Example 7 changes the mass ratio of glass fiber, modified silica and chitosan aqueous solution. As can be seen from Table 1, compared with Example 3, the residual monomer and thermal conductivity do not change much, but the values of flexural strength, compressive strength and tensile strength at break are significantly smaller than those of Examples 4-5, but larger than those of Examples 3 and 6, indicating that the modified silica is loaded on the surface and voids of the glass fiber to improve the strength of the glass fiber, and chitosan makes the modified silica and glass fiber more bonded, which subsequently improves the mechanical properties of expandable polystyrene, which is conducive to the application of expandable polystyrene.
[0081] In the preparation method of chitosan aqueous solution in Example 8, sodium alginate is not added. As can be seen from Table 1, compared with Example 3, the residual monomers and thermal conductivity do not change much, but the numerical changes of flexural strength, compressive strength and tensile strength at break are significantly reduced, indicating that sodium alginate has good film-forming and gel-forming abilities, and is mixed and cross-linked with chitosan to improve the viscosity of chitosan and form a gel-like structure, thereby increasing the viscosity of the system, which is subsequently helpful to improve the adhesion between glass fiber and modified silica.
[0082] Graphene is not added in the preparation method of modified silica in Example 9, and calcium stearate is not added in the preparation method of modified silica in Example 10. As can be seen from Table 1, compared with Example 3, the values of flexural strength, compressive strength and tensile strength at break are significantly greater than those in Example 4, but less than those in Example 3, indicating that graphene can be loaded on the surface of silica, increasing the tensile strength and impact strength of silica. Calcium stearate, as a surfactant, further improves the dispersibility of silica and graphene, makes graphene more evenly distributed on the surface of silica, improves the performance stability of modified silica, and subsequently helps to improve the mechanical properties and stability of glass fiber.
[0083] Example 12 changes the mass ratio of silica, graphene and calcium stearate. It can be seen from Table 1 that, compared with Example 1, the values of flexural strength, compressive strength and tensile strength at break are significantly greater than those of Examples 9-10, but less than those of Example 3, indicating that graphene can be loaded on the surface of silica, increasing the tensile strength and impact strength of silica. Calcium stearate makes silica and graphene evenly dispersed, making graphene more evenly distributed on the surface of silica. The combination of silica, graphene and calcium stearate improves the mechanical properties of silica, and subsequently improves the corresponding properties of glass fiber.
[0084] In Example 13, polyethylene wax is not added. As can be seen from Table 1, compared with Example 1, the residual monomer and thermal conductivity change greatly, and the values of flexural strength, compressive strength and tensile strength at break also decrease, indicating that the crystalline structure of polyethylene wax can promote the formation of bubble nuclei during the polymerization process of expandable polystyrene beads, improve the fluidity of expandable polystyrene beads, and help to improve production efficiency and product quality.
[0085] In Example 14, no phosphate is added. As shown in Table 1, compared with Example 1, the residual monomer is 0.08%, the thermal conductivity is 0.033 W / m﹒ k, and the flexural strength, compressive strength and tensile strength at break are all significantly changed, indicating that phosphate can promote the formation of pores and make the pores more uniform, thereby affecting the comprehensive properties of the expandable polystyrene material, such as density and strength.
[0086] In Example 15, potassium salt is not added. As can be seen from Table 1, compared with Example 1, the residual monomer and thermal conductivity change greatly, and the values of flexural strength, compressive strength and tensile strength at break also decrease, indicating that potassium salt promotes and controls the formation of polymer crystals, and as a heterogeneous nucleating agent, provides heterogeneous nucleation sites for crystallization, accelerates the crystallization process of the polymer, shortens the crystallization time, and subsequently improves the comprehensive properties of expandable polystyrene.
[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A process for producing packaging-grade expandable polystyrene particles, characterized in that: The steps include: (1) Mix pure water, emulsifier and dispersant evenly, control the pH to 7-9, add styrene monomer, then add nucleating agent, initiator and high impact polystyrene, start steam heating, control the temperature rise rate to 0.5-0.6℃ / min, the whole steam heating time is 1.5-2h, when the temperature reaches 84-85℃, stop steam, when the temperature reaches 87-89℃, circulate cooling water to maintain the temperature at 90±0.5℃; (2) Perform low-temperature granulation reaction. After the low-temperature granulation is completed, pentane is added to perform high-temperature reaction. The temperature is raised to 120.5-122.5°C at a rate of 0.5-0.6°C / min. The reaction time is 2.5-4h. The temperature is lowered to below 53°C. The calcium is neutralized with hydrochloric acid and washed. The washing pH is controlled to 4.0-6.
0. The product is separated and dried. An antistatic agent is sprayed. Secondary drying is performed. Screening is performed. An external lubricant is added to obtain the product.
2. A process for producing packaging-grade expandable polystyrene particles according to claim 1, characterized in that: The raw materials are as follows, calculated by weight: 104-106 parts of pure water, 0.002-0.003 parts of emulsifier, 0.1-0.2 parts of dispersant, 100-102 parts of styrene monomer, 0.28-0.36 parts of initiator, and 0.5-1 parts of high-impact polystyrene.
3. The production process of packaging-grade expandable polystyrene particles according to claim 1, characterized in that: The emulsifier is one or more of gelatin, cellulose, and polyvinyl alcohol; the external lubricant is one or more of mono- and di-glycerides of fatty acids, triolein, zinc stearate, and low-density polyethylene wax.
4. The production process of packaging-grade expandable polystyrene particles according to claim 1, characterized in that: The nucleating agent is 0.1-0.2 parts of polyethylene wax, 0.06-0.1 parts of phosphate, and 0.01-0.02 parts of potassium salt.
5. The production process of packaging-grade expandable polystyrene particles according to claim 1, characterized in that: The initiator is one or more of benzoyl peroxide, tert-butyl percarbonate, and tert-butyl perbenzoate.
6. The production process of packaging-grade expandable polystyrene particles according to claim 1, characterized in that: The dispersant is tricalcium phosphate or hydroxyapatite.
7. The production process of packaging-grade expandable polystyrene particles according to claim 1, characterized in that: In step (2), 6-10 parts of modified glass fiber are also added. The pretreatment method of the modified glass fiber comprises the following steps: dispersing the glass fiber in a citric acid solution, soaking for 1-2 hours, washing with water, and then dispersing it in deionized water, adding modified white carbon black, stirring evenly, filtering, and then spraying a chitosan aqueous solution, and drying to obtain the modified glass fiber.
8. The process for producing packaging-grade expandable polystyrene particles according to claim 7, characterized in that: The mass ratio of the glass fiber, modified white carbon black and chitosan aqueous solution is 1g:0.5-0.8g:0.03-0.06mL.
9. The process for producing packaging-grade expandable polystyrene particles according to claim 7, characterized in that: The preparation method of the modified white carbon black comprises the following steps: dispersing white carbon black in a silane coupling agent solution, stirring at a temperature of 70-75° C. for 1-2 hours, then adding graphene and calcium stearate, stirring evenly, and drying to obtain the modified white carbon black.
10. A process for producing packaging-grade expandable polystyrene particles according to claim 9, characterized in that: The mass ratio of white carbon black, graphene and calcium stearate is 1g:25-30mg:0.1-0.3g.
Citation Information
Patent Citations
Method for producing expandable styrene polymers
CN102791781A
Food-grade expandable polystyrene particles for food containers and preparation method thereof
CN102898673A
Preparation method for synthesizing expandable polystyrene through efficient composite fire retardation agent
CN103848934A
Production method for rapidly molding expandable polystyrene
CN106947175A
Production method of expandable polystyrene with high-foaming-multiplying power
CN107057106A
Cited By
Coating agent for expandable polystyrene particles as well as preparation method and application of coating agent
CN120349683A
